The Monarchy, republicanism and the Privy Council : the enduring cry for freedom - Robinson, Patrick (2012)
Argues that the monarchy in Jamaica should be replaced by a republican form of government and that the Privy Council should be replaced as the final appellate tribunal by the Caribbean Court of Justice.